DEVELOPMENT OF POST-ADOPTION BEHAVIOR MODELS FOR MOBILE WALLET USERS CONSIDERING QUALITY ASPECTS AND MODERATION OF MONETARY BENEFITS - Ardian Raharja, Aldi
M-wallet is one of the digital technology innovations that not only functions as a digital payment instrument, but can be seen as an information system (IS) in the form of a mobile device-based application that can also store money and various information including personal and transaction data. This study aims to analyze the effect of the quality aspect in m-wallet application services, especially those related to post-adoption behavior. Another objective of this research is to identify the dimensions that can describe the quality of cellular services which are specifically built with the m-wallet context. In addition, this study also analyzes the moderating effect of the monetary benefits obtained by users from discounts or promotions on their continuance use behavior. This study used 326 samples of m-wallet application user data in Indonesia which were collected through an online-based questionnaire. Structural Equation Modeling (SEM) is used to process data with several test procedures, namely testing the measurement model and testing the structural model. The results of the study indicate that the quality aspect has a complex influence on continuance intentions. On the other hand, the dimensions of perceived mobility, application design, reliability, customer service, and security/privacy are proven to be able to describe the concept of mobile service quality. Another finding is that the moderating effect of the monetary benefit variable is not proven to have an effect in the model built, both on the perceived usefulness relationship to continuance intention, and also on the satisfaction relationship with continuance intention.